What are Junior Infant teachers’ and early years educators’ opinions about informal and formal learning and the acquisition of academic skills for 4/5 year olds in the final year of pre-school? - O’Mahony, Helen (Marino Institute of Education, 2020)
This study aims to examine Junior Infant teachers’ and early years educators’ opinions about informal and formal learning and the acquisition of academic skills for 4/5 year olds in the final year of pre-school, in the context of concern that the two groups of professionals have a different understanding about what academic skills children should have on entering on primary school. This issue is important in the light of the need to ensure a smooth transition for children moving from pre-school to primary school. Quantitative data and qualitative data were collected via a questionnaire devised by the researcher from 45 early years professionals teaching on the ECCE scheme and 45 primary school teachers of Junior Infants. This study shows a clear difference of opinion between the early years educators and Junior Infant teachers in terms of which academic skills they see as important for 4/5 year olds leaving pre-school. Early years educators showed higher expectations of children’s learning outcomes than the Junior Infant teachers. The Junior Infant teachers expressed some concerns regarding the children’s learning of pre-academic and academic skills in pre-school, indicating that they found that they had to undo some of the children’s practices which they saw as incorrect. The study highlights the lack of a shared view on how and when academic skills should be introduced. A lack of communication and understanding between the two sectors was also evident and should be addressed.